Hubungan Tingkat Kecemasan Pre Anestesi Dengan Kejadian Mual Muntah Pada Durante Operasi Secsio Cessarea Dengan Sub Arachnoid Blok Anestesi Di Blud RSUD Martapura - Suhadi Suhadi; Ika Kusuma Wardani; Riska Eddela (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Background: The level anxiety is felt by many patients who will undergo surgery, hemodynamic instability due to pre-anesthesia anxiety have an impact on anesthetic complications and one of them is nausea and vomiting. Aim : To determine the correlation between pre-anesthesia anxiety level and the incidence of nausea and vomiting during section cesarean with Sub Arachnoid Block (SAB) spinal anesthesia. Methods: The research design was quantitative with a cross sectional approach. There were 97 respondents recruited as the sample through non-random sampling technique. Data were obtained from observation sheets and questionnaires. Finding : The finding indicated that the age of the respondents in this study was 17 to 48 years old. The majority of the respondents had mild anxiety levels (44.3%), did not experience anxiety (33.0%), moderate anxiety levels (18.6%), severe anxiety levels (4.1%). The respondents who did not experience nausea and vomiting (79.4%) and respondents who experienced nausea and vomiting (20.6%). Conclusion: Based on statistical test with Spearman's Rho obtained correlation coefficient value of 0.181 = weak correlation with SIG. 2-TAILED 0.076 (>0.05). In accordance with the correlation test data, it can be concluded that there is no significant or insignificant correlation between the level of pre-anesthesia anxiety with the incidence of nausea and vomiting in sectio caesarea with sub arachnoid block (SAB) spinal anesthesia at BLUD MartapuraHospital.